MODERN LEGISLATION REGULATING STATUS OF LEGAL ENTITY - Zhylkichieva K. S.; Kalybaeva A. A.; Koshokova G. Zh. (Scientific Journal of Pedagogy and Economics, 2021)
The article analyzes using the normative and systematic methods, as well as analysis and synthesis, the content of the statements of Constitution of the Kyrgyz Republic, Civil Code of the Kyrgyz Republic, Criminal Code of the Kyrgyz Republic, the Law of the Kyrgyz Republic «About Normative Legal Acts of the Kyrgyz Republic», the Law of the Kyrgyz Republic «On the Regulations of the Jogorku Kenesh of the Kyrgyz Republic» and the works of the legal scholars. It examined the provisions of laws adopted for general regulation and concludes they are serious problems, because of them there is a "blurring" of the contour of the legislation on legal entities in the article. The publication supports the opinion of the authors of the Concept for Development, according to which the regulation of the status of legal entities in the civil legal field can be characterized by a set of the laws and regulations in force in the Kyrgyz Republic, which do not always correspond to each other, as well as to the Civil Code. The low legal and technical level and ineffectiveness in practice are also shown by some adopted laws. It noted the Civil Code of the Kyrgyz Republic, adopted on May 8, 1996, created the new foundation for the regulation of legal entities, which was supplemented by many new laws over the next decades in the article. The authors come to the conclusion the fairly honest assessment can be applied to the established regulation – that with the main vector of development of the Concept of Civil Legislation in Kyrgyzstan, in general, there is an economic, social and well-grounded the logic and generally justifiable modern civil law in relation to legal entities. But at the same time, for many problems, correct solutions have not yet been found and no efficiency ratings have been given.